Case Report: Diagnosis and Assessment of Cure Approaches for Acute Schistosomiasis in Pre-School Children - Cavalcanti, Marta G.; Engel, Délia Celser; de Araujo Cunha, Aline Fernandes; Peralta, José Mauro (Frontiers in Immunology, 2021)
Acute Schistosoma (AS) infection manifests with a broad spectrum of clinical features in the paediatric populations. Diagnosis may be difficult in the absence of detectable eggs. As a result, new approaches may be required to achieve an accurate diagnosis. Ideal praziquantel (PZQ) treatment regimen for young children is debatable. Also, the post-treatment response is still poorly evaluated because of a lack of reliable markers. A group of 6 children – a toddler, 4 pre-school children and one pre-adolescent were investigated for AS clinical manifestations and followed-up for two years. Ova detection was performed by Kato-Katz (KK) and Schistosoma DNA by real-time PCR (rt-PCR) in stool samples. IgG and IgE anti-Schistosoma levels and urinary antigen were detected by ELISA and point-of-care circulating cathodic antigen (POC-CCA) in serum and urine, respectively. In 5/7, children presented mild to moderate intensity symptoms and increased leukocyte and eosinophil counts. The KK test was positive in 3/7 and serology, 4/7 children. rt-PCR was reactive in 6/7 children while urinary antigen was detected in the whole group. After three sequential doses of PZQ (80mg/kg/dose), KK and rt-PCR indicated cure rates (CR) of 100% and 85.7%, respectively. The CR determined by POC-CCA ranged from 28.6-100%. The results suggest that high dose and repeated treatment with PZQ might be effective for AS in young children. Also, new laboratory markers should be considered to diagnosis and monitor the drug response.